Contribution of grazing to soil atmosphere CH4 exchange during the growing season in a continental steppe - Tang S; Wang C; Wilkes, Andreas; Zhou P; Jiang Y; Han, G.; Zhao M; Huang D; Schönbach, P. (Elsevier, 2013)
Degradation of steppes induced by overgrazing may affect the uptake of atmospheric methane (CH4) by soil sinks. However, uncertainty is associated with the very limited knowledge of gas fluxes in rapidly degrading steppe. In this study, we investigated the effects of grazing on CH4 uptake during the growing season in three types of steppe (meadow steppe, typical steppe and desert steppe and) in Inner Mongolia, China, to quantify and compare CH4 uptake in steppe ecosystems under different grazing management conditions. The CH4 fluxes were measured using an automatic cavity ring-down spectrophotometer at three steppe locations that differed primarily in grazing intensity. The results indicated that steppe soils were CH4 sinks throughout the growing season. CH4 uptake at all sites averaged 7.98 kg CH4-C ha−1 yr−1 (ranging from 1.53 to 18.74 kg CH4-C ha−1 yr−1), of which approximately 43.8% occurred in the desert steppe. CH4 uptake in the desert steppe increased 20.4% and 51.2% compared with the typical steppe and meadow steppe, respectively. Light grazing (LG) of steppe did not significantly change CH4 uptake compared with un-grazed (UG) steppe, but moderate and heavy grazing (MG, HG) reduced CH4 uptake significantly (by 6.8–37.9%, P < 0.05). These findings imply that reducing the grazing pressure on steppe would help increase the atmospheric CH4 sinks in steppe soils. Our results suggest that HG exerts a considerable negative impact on CH4 uptake in a continental steppe. Further studies involving year-round, intensive measurements of CH4 uptake are needed.